Peran KPK dalam Menangani Kasus Dugaan Korupsi Pertamina dalam Sistem Pidana Khusus - Adia Talitha; Dimas Ramdhani Abimanyu Permadi; Sanesa Putri Vinata; Cantika Putri Tuti Susanti; Nabila Aprilia Arianto; Enggar Dwi Hartono; Ferdiansyah Ferdiansyah; Muhammad Hajer (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Corruption is an abuse of power, the impacts of corruption include damaging democratic values, morality, harming the state financial system, violating the social and economic rights of the community and being a threat to the ideals of a just and prosperous society. This can be seen from the cases of corruption that have been successfully uncovered by the KPK, namely the corruption of Pertamina which has been prosecuted at the Central Jakarta District Court. The method used is normative legal research with a statutory regulatory approach. This research aims to prevent significant state losses, ensure the accountability of public officials, and maintain the integrity of the company. In addition, this effort is to create public trust in the management of national energy resources. The results of the study show that this process involves coercive measures recorded in the examination report. The Attorney General's Office is currently examining eight witnesses, including Fitra Eri, in a case of alleged corruption related to the management of crude oil and refinery products of PT Pertamina (Persero)..